DEEP WEATHERING THROUGH TIME IN CENTRAL AND NORTHWESTERN EUROPE: PROBLEMS OF DATING AND INTERPRETATION OF GEOLOGICAL RECORD - Migon P.; Lidmar-Bergstrom K. (My University, 2002)
Upland and shield areas of central and northwestern Europe are characterised by an abundance of relict weathering mantles (saprolites). These saprolites, if accurately dated and interpreted, may serve as an important complementary source of information about long-term environmental history. In this paper, methods used to establish ages of weathering mantles are reviewed, such as stratigraphic and morphostratigraphic dating, clay mineral and stable isotope analysis, K-Ar and cosmogenic isotope dating, particularly with reference to European examples. The record of deep weathering in the Mesozoic and Cainozoic is examined to explain the peculiarities of the evidence and controls on the changing style of weathering through time. Weathering has been a continuous process through time, but general and local geological conditions have resulted in different ages of preserved mantles. An apparent trend from an earlier kaolinitic/ferrallitic style of weathering in the Mesozoic and Early Tertiary, towards a grussic style by the end of the Cainozoic, does not only reflect climate change, but it is also broadly consistent with tectonic/geomorphic history and related changes in land surface stability. Miocene and Plio-Pleistocene saprolites, in particular, show that in different geomorphological and lithological circumstances, different types of weathering mantles could have evolved.
Keywords: WEATHERING; SAPROLITES; DATING METHODS; EUROPE; Mesozoic; Pleistocene; Miocene; Mesozoic; Кайнозой::Неоген::Миоцен; Cenozoic::Quaternary::Pleistocene; Мезозой; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Neogene::Miocene